Reputasi Universitas, Biaya Kuliah, Fasilitas Perkuliahan dan Keputusan Mahasiswa Memilih Program Studi Manajemen Universitas Flores: Studi Pada Mahasiswa Program Studi Manajemen Angkatan 2019 - Yosafat Kristianus Bao; Maria Helena Carolinda Dua Mea (ANALISIS, 2020)
The decision to study in a major is a big challenge among most students. They will consider the existing conditions or circumstances. If the circumstances or conditions seem not in accordance with what is expected, there will be doubts which result in the decision not to choose the expected study program. Although in making a decision to take education in a study program, a consideration is needed, however, students of the Management study program have not conducted an analysis of the study program they are taking. The research approach used is a quantitative approach. From the calculation, the t-count value is 19.794 with a significance level of 0.000 or a sig value <0.05, the first hypothesis which states "the reputation of the university affects the student's decision to choose Management Study Program at the University of Flores" is accepted. From the calculation results, the t-count value is 0.887 with a significance level of 0.377 or sig> 0.05, thus the second hypothesis which states "tuition costs affect students' decisions to choose Management Study Program at the University of Flores" is rejected. From the calculation results, it is obtained that the t-count value is 5.295 with a significance level of 0.000 or a sig value <0.05, the third hypothesis which states "lecture facilities affect the student's decision to choose Management Study Program at the University of Flores" is accepted.